Gershwin: in de spiegel van zijn tijd - Jablonski, Edward (Haarlem Gottmer, 1993)
Publicist Edward Jablonski, who specializes in 20th-century American music, has compiled a portrait of American composer and pianist George Gershwin (1898-1937). He does so using documents by contemporaries Ira Gershwin, Fred Astaire, Jerome Swift and Irving Berlin and many others. The texts are arranged chronologically. Therefore, the book can be read as a life cycle of the composer. The book is illustrated, has notes and an index.
Keywords: Gershwin, George -- 1898-1937; 20th Century (1901-2000); Composer; Biography; Music history